Implementation of Lean Manufacturing, VSM, FMEA, and RCA to Reduce Waste in Fertilizer Production - Endang Agustina; Joumil A Saifudin (Faculty of Engineering, Universitas Muhammadiyah Jakarta, 2025)
This study aims to minimize waste in the production of Phonska IV subsidized compound fertilizer by implementing an integrated Lean Manufacturing approach. The methodology combines Value Stream Mapping (VSM), Failure Mode and Effect Analysis (FMEA), and Root Cause Analysis (RCA). Value Stream Analysis Tool (VALSAT) was employed to identify non-value-added activities, revealing four dominant wastes: waiting, defects, excess processing, and overproduction. Root causes were investigated using fishbone diagrams, and risks were prioritized via FMEA based on the Risk Priority Number (RPN). Implemented countermeasures included standardizing raw material checks, validating materials pre-mixing, scheduling preventive maintenance, and adopting demand-driven production planning. These interventions reduced the total production cycle time from 215 minutes to 150 minutes, achieving a 30.2% efficiency improvement. The study demonstrates the practical efficacy of integrating VSM, RCA, and FMEA in a continuous-process industry and contributes a structured model for systematic waste reduction in subsidized fertilizer manufacturing.